EXPLORATORY FACTOR ANALYSIS (EFA) OF PERFORMANCE OF SMES - Dede Ansyari Guci - (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
Performance of SMEs in Indonesia has been a lot of research on previous study. The objective of this research is to develop an idea for calculate performance of SMEs. As many as 100 respondents of pilot test of  SME players in Medan, Indonesia. The validation method aimed at validating the parameters  which  calculate each of the constructs by statitiscally determining that the sample is adequate, using KMO and barlett’s test to confirm the effectiveness of the data for multivariate statistical analysis, validating the calculation requirements as applicable to performance of SMEs adept. The result show that the data is valid and reliable design.